Self-Esteem and Celebrity Worship on Late Adolescents - Kusuma, Lily; Yuliawati, Livia (Faculty of Psychology, Universitas Surabaya, 2013)
Individuals who have their favourite celebrity are commonly found in our society. To some extent, to have a favourite celebrity is considered normal. However, this can become abnormal if the individual is obsessed with his/her favourite celebrity. This phenomenon is called celebrity worship. Celebrity worship consists of three levels: entertainment-social (ES), intense-personal (IP), and borderline-pathological (BP). This phenomenon can happen to an individual with unhealthy self-esteem, who lacks of social relationship in his or her life. The aim of this study was to find out the relationship between self-esteem and each level of celebrity worship on late adolescents. College students (N=266) were chosen as samples of the study. Results reveal no significant correlation between self-esteem and entertainment-social (ES) celebrity worship. It also showed that there was no significant correlation between self-esteem and intense-personal (IP) celebrity worship. Finally, there was negative correlation between self-esteem and borderline- pathological (BP) celebrity worship (r= - ,138). Dalam kehidupan sehari-hari, tidak jarang dijumpai individu yang memiliki selebriti favorit yang tentunya merupakan suatu hal yang wajar. Namun, keadaan ini akan menjadi tidak wajar bila individu tersebut terobsesi dengan selebriti favoritnya. Fenomena ini disebut sebagai pemujaan selebriti (celebrity worship). Pemujaan selebriti terdiri atas tiga tingkatan, yaitu entertainment- social (ES), intense-personal (IP), dan borderline-pathological (BP). Individu dengan self-esteem yang tidak sehat dapat memuja selebriti favoritnya karena kurangnya relasi sosial yang terjalin di dunia nyata. Penelitian ini bertujuan mengetahui hubungan antara harga diri (self-esteem) dan ketiga tingkat pemujaan selebriti pada remaja akhir. Sampel pada penelitian ini adalah 266 mahasiswa. Hasil menunjukkan tidak ada hubungan yang signifikan antara harga diri dan pemujaan selebriti tingkat ES dan tingkat IP. Namun, terdapat korelasi negatif antara harga diri dan pemujaan selebriti tingkat BP (r= - .138).